Manajemen Team Teaching di Madrasah Ibtidaiyah - Ferina Widyawati; Saiful Anwar; Happy Susanto; Rohmadi Rohmadi (Jurnal Riset Madrasah Ibtidaiyah, 2022)
MI Muhammadiyah 6 Nglegok Jenangan Ponorogo is an educational institution under the auspices of the world's largest organization, Muhammadiyah. In their learning, MI Muhammadiyah 6 Nglegok Jenangan Ponorogo uses the Team Teaching method so that the teaching and learning process can run well and by the targets set by the madrasa. This study aims to describe the management of Team Teaching, the supporting and inhibiting factors of Team Teaching management at MI Muhammamdiyah 6 Nglegok Jenangan Ponorogo. This research is qualitative research with a descriptive approach directed to the field and uses a general system that does not require a theoretical study. In this research, the data collection uses interview, observation, and documentation methods to answer the management of Team Teaching at MI Muhammadiyah 6 Nglegok Jenangan Ponorogo. The results of this study were concluded as follows: (1) Management of the Teaching Team at MI Muhammadiyah 6 Nglegok Jenangan Ponorogo in one class led by two teachers, where one teacher focused on etiquette and general subjects, while the other teacher focused on al Qur'an or tahfidz and spiritual lessons; (2) Supporting factors in implementing the Team Teaching method in madrasas are the existence of a development team, Madrasa Heads, Teachers, Students and also adequate infrastructure, while the inhibiting factor is the lack of communication with parents so that there are still many parents who do not understand the program. Is in the Madrasa.